OP0263 First Results from "Be-Giant": Baseline Characteristics of an Early Spondyloarthritis Cohort. (10th June 2014) - Varkas, G.; Cypers, H.; Van Praet, L.; Carron, P.; Raeman, F.; Gyselbrecht, L.; Devinck, M.; Corluy, L.; Vanneuville, B.; Elewaut, D.; Van den Bosch, F.
Abstract : Background: The underlying idea for the development of the ASAS classification criteria for Spondyloarthritis (SpA) was to allow earlier recognition and diagnosis of patients with axial and/or peripheral SpA, given the known long delay between symptom onset and definitive diagnosis when modified New York (mNY) criteria for ankylosing spondylitis are used [1]. However, diagnosis at an early disease stage automatically leads to a more heterogeneous population, including patients with less severe disease manifestations. One of the major current challenges in the field of SpA is the study of the natural evolution of these early patients, including the identification of prognostic factors and biomarkers of disease activity. Methods: The BelGian Inflammatory Arthritis and spoNdylitis cohorT (Be-Giant) is a multicentre, observational cohort that includes consecutive patients, diagnosed with SpA by their treating rheumatologist. Patients that fulfill the ASAS classification criteria, are prospectively followed every 6 months: this includes patient-reported outcomes, a standardized clinical examination (peripheral joints, entheses, axial metrology), laboratory variables and imaging. Patients already fulfilling the mNY criteria at baseline are excluded. Results: We report the baseline characteristics of the first 122 newly diagnosed SpA patients (Table 1 ). In the non-radiographic axial SpA (nr-axSpA) patients, a high prevalence of HLA B27 as well as a positive MRI of the sacroiliac joints, as defined by the ASAS criteria was noted. Consistent with other early cohorts, we found a slightly higher prevalence of female patients. Considering extra-articular manifestations, psoriasis was more prevalent in peripheral SpA, whereas uveitis was more prevalent in nr-axSpA. Inflammatory bowel disease was similar in both groups. Nr-axSpA and peripheral SpA patients have a similar burden of disease as reported by BASDAI, BASFI, HAQ. SF36 was significantly higher in nr- axSpA (P=0.032). Conclusions: Be-Giant is a new cohort in which patients that are diagnosed by rheumatologists as early SpA are prospectively followed. To our knowledge, this is a unique population, which will allow to study the natural evolution of patients classified according to the ASAS criteria. Baseline characteristics are completely in line with other early SpA cohorts. An indisputable asset is the high prevalence of classification through the imaging arm of the ASAS criteria in up to 85%. References: Sieper J, Rudwaleit M, Baraliakos X, et al. The Assessment of SpondyloArthritis international Society (ASAS) handbook: a guide to assess spondyloarthritis. Ann Rheum Dis 2009;68(Suppl 2):ii1-ii44. Acknowledgements: The Be-Giant cohort is funded by an unrestricted grant by AbbVie. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4951